1998
DOI: 10.1038/emm.1998.38
|View full text |Cite
|
Sign up to set email alerts
|

Calpain inhibitors reduce the cornified cell envelope formation by inhibiting proteolytic processing of transglutaminase 1

Abstract: Calpain I ( -calpain) and II (m-calpain) are well known calcium-activated neutral cysteine proteases. Many reports have shown that activation of calpain is related to cataract formation, neuronal degeneration, blood clotting, ischemic injuries, muscular dystrophy and cornified cell envelope (CE) formation. Here, we report that insoluble CE formation was reduced after treatment with calpain I inhibitor (N-acetyl-leucylleucyl-norleucinal) on normal human epidermal keratinocytes (NHEK), whereas serine and thiol p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Topical applications of H1r and H2r antagonists enhanced epidermal differentiation, the latter at both the mRNA and protein levels, which could reflect the ability of these agents to mobilize intracellular calcium (Koizumi and Ohkawara, 1999). Enhanced differentiation translated further into a significant increase in the thickness of cornified envelopes, which should yield more robust corneocytes, also a Ca ++ -dependent process (Kim and Bae, 1998, Nemes and Steinert, 1999). The converse certainly proves this point -- effete cornified envelopes occur in several inherited disorders of cornification, including loss-of-function mutations in transglutaminase 1-deficient (lamellar) ichthyosis [rev.…”
Section: Discussionmentioning
confidence: 99%
“…Topical applications of H1r and H2r antagonists enhanced epidermal differentiation, the latter at both the mRNA and protein levels, which could reflect the ability of these agents to mobilize intracellular calcium (Koizumi and Ohkawara, 1999). Enhanced differentiation translated further into a significant increase in the thickness of cornified envelopes, which should yield more robust corneocytes, also a Ca ++ -dependent process (Kim and Bae, 1998, Nemes and Steinert, 1999). The converse certainly proves this point -- effete cornified envelopes occur in several inherited disorders of cornification, including loss-of-function mutations in transglutaminase 1-deficient (lamellar) ichthyosis [rev.…”
Section: Discussionmentioning
confidence: 99%
“…During terminal differentiation, full-length TGase 1 proteins undergo proteolytic cleavage, leading to ϳ100 to 1000-fold higher specific activity (42,43). Calpain, a Ca 2ϩ -dependent protease, may activate TGase 1 in vivo (44,45), and microarray analyses of Hoxb13 knock-out versus wild-type skin (24) revealed that calpain expression is significantly reduced in the Hoxb13 knock-out (data not shown). Finally, it is interesting to note that another Hox protein, HoxA7, down-regulates TGase 1 expression at the transcriptional level, and inhibits differentiation (46).…”
Section: Discussionmentioning
confidence: 99%
“…In keratinocytes, most of the newly synthesized TG-1 is attached to membrane and therefore the possible mechanism of its cleavage by lysosomal CD remains ambiguous [102]. Moreover, the role of cytoplasmic caplain in TG-1 processing and cornified envelope formation has also been demonstrated [103].…”
Section: Mechanisms Of Neuronal and Retinal Cell Death In CD Knock-oumentioning
confidence: 99%